Modeling for analysis of the effect of Young's modulus on soft active hydrogels subject to pH stimulus - Li, Hua; Yew, Yong Kin; Ng, Teng Yong (Smart materials and structures, 2009)
Modeling is conducted in this paper for analysis of the influence of Young's modulus on the response of soft active hydrogels to environmental solution pH changes. A chemo-electro-mechanical formulation termed the multi-effect-coupling pH-stimulus (MECpH) model, which was developed previously according to linear elastic theory for small deformation description, is improved in this paper through incorporation of the finite deformation formulation into the mechanical equilibrium equation. The model is expressed by coupled nonlinear partial differential equations and solved via the meshless Hermite-cloud method with the modified Newton iteration technique. The improved MECpH model is examined by comparison between the computational and published experimental results. Numerical studies are then done on the influence of Young's modulus on the distributive variations of the diffusive ion concentrations and electric potential, and on the deformation variations of the pH-stimulus-responsive hydrogels within different buffered solutions.